Persister cells in a biofilm treated with a biocide - Simões, Lúcia C. (2011)
This study investigated the physiology and behaviour following treatment with ortho-phthalaldehyde (OPA), of Pseudomonas fluorescens in both the planktonic and sessile states. Steady-state biofilms and planktonic cells were collected from a bioreactor and their extracellular polymeric substances (EPS) were extracted using a method that did not destroy the cells. Cell structure and physiology after EPS extraction were compared in terms of respiratory activity, morphology, cell protein and polysaccharide content, and expression of the outer membrane proteins (OMP). Significant differences were found between the physiological parameters analysed. Planktonic cells were more metabolically active, and contained greater amounts of proteins and polysaccharides than biofilm cells. Moreover, biofilm formation promoted the expression of distinct OMP. Additional experiments were performed with cells after EPS extraction in order to compare the susceptibility of planktonic and biofilm cells to OPA. Cells were completely inactivated after exposure to the biocide (minimum bactericidal concentration, MBC ¼ 0.55 + 0.20 mM for planktonic cells; MBC ¼ 1.7 + 0.30 mM for biofilm cells). After treatment, the potential of inactivated cells to recover from antimicrobial exposure was evaluated over time. Planktonic cells remained inactive over 48 h while cells from biofilms recovered 24 h after exposure to OPA, and the number of viable and culturable cells increased over time. The MBC of the recovered biofilm cells after a second exposure to OPA was 0.58 + 0.40 mM, a concentration similar to the MBC of planktonic cells. This study demonstrates that persister cells may survive in biocide-treated biofilms, even in the absence of EPS.